Visible-Light-Promoted Indole C-3 Formylation Using Eosin Y as a Photoredox Catalyst - Zhao, Yin; Li, Hongfang; Yin, Shan; Wu, Yandan; Ni, Guanghui (Synlett, 2022)
A visible-light-mediated C-3 formylation of indole catalyzed by eosin Y has been developed using tetramethylethylenediamine as a carbon source and air as an oxidant. This protocol shows high tolerance to a large quantity of functional groups under mild conditions and provides 3-formylated indoles with good yields. This method is a highly attractive alternative to the approach of traditional formylation.
Keywords: visible light; eosin Y; air oxidant; indole formylation; photoredox